Analisis Variasi Jenis Elektroda Buffer Layer Pada Proses Hardfacing Material ASTM A216 WCB Terhadap Uji Visual, Uji Penetran Dan Makro - Toto, Alvalo; Al Amin, Mochammad Karim; Wahyudi, M. Thoriq; Budi Kurniyanto, Hendri; Amri, Moh. Syaiful; Firmansyah, Moch. Aria; Leonard, Rikky (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2026)
ASTM A216 WCB is a cast carbon steel material commonly used in valve components due to its good mechanical properties and resistance to high temperatures. One of the major issues encountered in its application is surface wear. To enhance surface hardness and wear resistance, a hardfacing process was conducted using the GTAW welding method. This involved the application of buffer layers using ER308 and ER309 filler metals, followed by hardfacing layers of Stellite 12. A total of four specimens were prepared with varying combinations of buffer and hardfacing layer numbers. The visual inspection results indicated the absence of surface defects in all specimens, demonstrating good welding quality. Dye penetrant testing revealed a non-relevant indication on specimen 3 with a size of 1.3 mm, which remains within the acceptable limits as per ASME Section IX standards. Macroscopic examination showed sound fusion between layers, free from defects such as porosity or cracks. The deepest weld penetration was observed in specimen 4, which used the ER309 buffer layer, achieving a depth of 1.5 mm. Overall, the use of ER308 and ER309 buffer layers significantly influenced the quality of the hardfacing welds, contributing to the formation of homogeneous and defect-free layers. This study provides valuable insight into material selection and welding parameters to improve wear resistance in ASTM A216 WCB-based valve components within industrial environments.